Analysis of Factors Affecting Business Income in the Fish Satay MSME Sector in Tanjung Village, North Lombok Regency - Patrasia, Tena; Fadliyanti, Luluk; Husni, Vici Handalusia (The Es Economics and Entrepreneurship, 2024)
This study analyzes the effect of business capital, labor, and working hours on income in fish satay UMKM in Tanjung Village, North Lombok Regency. This study uses a quantitative research type with primary data. Data were obtained from the results of the questionnaire, the number of data obtained was 31 respondents. The analysis tools used were multiple linear regression, determination coefficient test (R2), t test and simultaneous coefficient significance test (f test). The results of this study indicate that the variables of business capital, labor, and working hours simultaneously have a significant effect on business income. While the R2 value is 0.808, this means that 8.8% of business income is influenced by the variables above, the rest is influenced by other variables outside this study.